2021
DOI: 10.52403/ijhsr.20210515
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer in Women: Epidemiological, Histological, Immunohistochemical and Molecular Sub-Types in the Republic of Congo

Abstract: Introduction: Breast cancer is a heterogeneous disease with a variety of morphological, molecular, treatment response and clinical outcome characteristics. The objective of this work was to assess the epidemiological, histological, immunohistochemical and molecular subtypes of breast cancer in women in the Republic of Congo. Material and Methods: We carried out a cross-sectional descriptive study which took place from January 1, 2014 to December 31, 2020. The study focused on 150 cases of breast cancer in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Moderately differentiated (grade II) BC was found in most (49.6%) patients. This result agreed with other studies conducted by Gemta et [13,25,27,[30][31][32][33][34][35][36][37]. Conversely, poorly differentiated (grade III) BC was common in another study conducted in Ghana (49%) [30].…”
Section: Clinicopathological Featuressupporting
confidence: 91%
See 1 more Smart Citation
“…Moderately differentiated (grade II) BC was found in most (49.6%) patients. This result agreed with other studies conducted by Gemta et [13,25,27,[30][31][32][33][34][35][36][37]. Conversely, poorly differentiated (grade III) BC was common in another study conducted in Ghana (49%) [30].…”
Section: Clinicopathological Featuressupporting
confidence: 91%
“…Moderately differentiated (grade II) BC was found in most (49.6%) patients. This result agreed with other studies conducted by Gemta et al, Hadi and Jamal, Takalkar et al, Pathak et al, Toma et al, Malanda et al, Adeniji et al, Ezike et al, Zilenaite et al, Uyisenga et al and Maffuz-Aziz et al, who reported 46.2%, 47.3%, 75.4%, 76.8%, 53.8%, 51,3%, 52.6%, 59.5%, 46.5%, 52.9%, and 54.1% of grade II tumor, respectively [ 13 , 25 , 27 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Conversely, poorly differentiated (grade III) BC was common in another study conducted in Ghana (49%) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings regarding the impact of family history align with recent studies, which reported a similar trend. The study by Mboungou Malanda et al [35] noted that only 11 cases, accounting for 7.33%, had a family history of breast cancer. Likewise, another study by Gautam et al [36] found that 10.4% of patients had a family history of breast cancer, while the majority, 89.6%, had no family history of breast cancer.…”
Section: F Family History Distributionmentioning
confidence: 99%